Estimated Glomerular Filtration Rate Is an Easy Predictor of Venous Thromboembolism in Cancer Patients Undergoing Platinum-Based Chemotherapy. (7th April 2014) - Ferroni, Patrizia; Guadagni, Fiorella; Laudisi, Anastasia; Vergati, Matteo; Riondino, Silvia; Russo, Antonio; Davì, Giovanni; Roselli, Mario
Abstract: Background: Reduced estimated glomerular filtration rate (eGFR) has been associated with increased venous thromboembolism (VTE) risk in the general population. VTE incidence significantly increases in cancer patients, especially those undergoing chemotherapy. Despite the evidence that a substantial number of cancer patients have unrecognized renal impairment, as indicated by reduced eGFR in the presence of serum creatinine levels within the reference value, chemotherapy dosage is routinely adjusted for serum creatinine values. Among chemotherapies, platinum-based regimens are associated with the highest rates of VTE. A cohort study was designed to assess the value of pretreatment eGFR in the risk prediction of a first VTE episode in cancer outpatients without previous history of VTE who were scheduled for platinum-based chemotherapy. Methods: Serum creatinine and eGFR were evaluated before the start of standard platinum-based chemotherapy in a cohort of 322 consecutive patients with primary or relapsing/recurrent solid cancers, representative of a general practice population. Results: Patients who experienced a first VTE episode in the course of chemotherapy had lower mean eGFR values compared with patients who remained VTE free. Multivariate Cox analysis demonstrated that eGFR had an independent value for risk prediction of a first VTE episode during treatment, with a 3.15 hazard ratio. Indeed, 14% of patients with reduced eGFR had VTE over 1-year follow-up compared with 6% of patients with normal eGFR values. Conclusion: The results suggest that reductions in eGFR, even in the presence of normal serum creatinine, are associated with an increased VTE risk in cancer outpatients undergoing platinum-based chemotherapy regimens. Determining eGFR before chemotherapy could represent a simple predictor of VTE, at no additional cost to health care systems. Abstract : There is a common need to identify risk assessment models that may be predictive of cancer-associated venous thromboembolism in at-risk patients who might benefit from appropriate prevention measures. Assessment of pretreatment estimated glomerular filtration rate could represent a simple and cost-effective predictor of venous thromboembolic events, at no additional cost to health care systems.